2013
DOI: 10.1053/j.gastro.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

GS-9620, an Oral Agonist of Toll-Like Receptor-7, Induces Prolonged Suppression of Hepatitis B Virus in Chronically Infected Chimpanzees

Abstract: Background & Aims Direct-acting anti-viral agents suppress hepatitis B virus (HBV) load but must be given lifelong. Stimulation of the innate immune system could increase its ability to control the virus and have long lasting effects, after a finite regimen. We investigated the effects of immune activation with GS-9620—a potent and selective orally active small molecule agonist of Toll-Like Receptor (TLR)7—in chimpanzees with chronic HBV infection. Methods GS-9620 was administered to chimpanzees every other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
288
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(300 citation statements)
references
References 34 publications
7
288
1
4
Order By: Relevance
“…Recently, oral TLR7 ligands successfully induced viral control in Woodchuck and chimpanzee HBV-animal models (Menne et al, 2015;Lanford et al, 2013). Disappointingly in humans, oral TLR7 ligands thus far have not achieved any beneficial effect, despite that treatment was well tolerated (Gane et al, 2015;Janssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oral TLR7 ligands successfully induced viral control in Woodchuck and chimpanzee HBV-animal models (Menne et al, 2015;Lanford et al, 2013). Disappointingly in humans, oral TLR7 ligands thus far have not achieved any beneficial effect, despite that treatment was well tolerated (Gane et al, 2015;Janssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have the potential to influence the nature of innate immune responses during infection and are a primary target of new synthetic Toll-like receptor(TLR)-based antivirals. 20 Similar to mDCs, the majority of studies have found that the frequency of pDCs was similar between chronic HBV patients and healthy donors (Table 2). 14-17,21-23 As noted above for mDCs, this result was consistent for adults, pediatric patients 12 and infants born to HBV-positive mothers.…”
Section: Overviewmentioning
confidence: 91%
“…T cells [51]. TLR7 agonist administered orally to chimpanzees was observed to stimulate IFN-a production and the activation of ISGs and NK cells, resulting in prolonged suppression of HBV [52]. Blockade of programmed cell death (PD)-1 protein is an alternative and promising approach in chronic HBV infection.…”
Section: Immunological Intervention Against Hbv Infectionmentioning
confidence: 99%